Ընկուզենու ծիսապաշտամունքային գործառոյթներ եւ հաւատալիքներ - Աբրահամեան, Յասմիկ (տպ. Atlas)
Pantheistic phenomena have always been an important component of spiritual culture due to various uses of natural resources in general and vegetation in particular, including the use of different types of trees. The rituals and beliefs connected to the walnut tree are among the most common in the Syunik region in Armenia. The paper is based on ethnographic field work conducted between 2021 and 2023 in thirty urban and rural settlements of the Syunik. Collected ethnographic materials and published sources testify that the sanctity of the walnut tree in Syunik has two main expressions: 1) the connection of the tree to canonic and non-canonical shrines around which rituals are performed; 2) the beliefs connected to the tree. The walnutrelated beliefs may be grouped as a) viable beliefs, b) beliefs present only in memories, c) forgotten beliefs (recorded in publications), d) beliefs formed in the present days. This study concludes that the non-material cultural traditions connected to the walnut tree in Syunik continue existing in the form of passive beliefs transmitted by oral lore and in the form of living practices. 36
Keywords: Ազգագրութիւն; Բանահիւսութիւն